Co-crystallization of a neutral molecule and its zwitterionic tautomer: structure and Hirshfeld surface analysis of 5-methyl-4-(5-methyl-1H-pyrazol-3-yl)-2-phenyl-2,3-dihydro-1H-pyrazol-3-one 5-methyl-4-(5-methyl-1H-pyrazol-2-ium-3-yl)-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-1-ide monohydrate - Asiri, Abdullah M.; Alzahrani, Khalid A. H.; Faidallah, Hassan M.; Alamry, Khalid A.; Jotani, Mukesh M.; Tiekink, Edward R. T. * (International Union of Crystallography, 2019)
The title compound, 2C14H14N4OH2O, comprises a neutral molecule containing a central pyrazol-3-one ring flanked by an N-bound phenyl group and a C-bound 5-methyl-1H-pyrazol-3-yl group (at positions adjacent to the carbonyl substituent), its zwitterionic tautomer, whereby the N-bound proton of the central ring is now resident on the pendant ring, and a water molecule of crystallization. Besides systematic variations in geometric parameters, the two independent organic molecules have broadly similar conformations, as seen in the dihedral angle between the five-membered rings [9.72 (9) for the neutral molecule and 3.32 (9) for the zwitterionic tautomer] and in the dihedral angles between the central and pendant five-membered rings [28.19 (8) and 20.96 (8) (neutral molecule); 11.33 (9) and 11.81 (9)]. In the crystal, pyrazolyl-N—HO(carbonyl) and pyrazolium-N—HN(pyrazolyl) hydrogen bonds between the independent organic molecules give rise to non-symmetric ninemembered HNNHNC3O and HNNHNC3O synthons, which differ in the positions of the N-bound H atoms. These aggregates are connected into a supramolecular layer in the bc plane by water-O—HN(pyrazolide), waterO—HO(carbonyl) and pyrazolyl-N—HO(water) hydrogen bonding. The layers are linked into a three-dimensional architecture by methyl-C—H(phenyl) interactions. The different interactions, in particular the weaker contacts, formed by the organic molecules are clearly evident in the calculated Hirshfeld surfaces, and the calculated electrostatic potentials differentiate the tautomers.